2019
DOI: 10.1038/s41431-019-0399-0
|View full text |Cite
|
Sign up to set email alerts
|

Y-chromosomal analysis of clan structure of Kalmyks, the only European Mongol people, and their relationship to Oirat-Mongols of Inner Asia

Abstract: Kalmyks, the only Mongolic-speaking population in Europe, live in the southeast of the European Plain, in Russia. They adhere to Buddhism and speak a dialect of the Mongolian language. Historical and linguistic evidence, as well a shared clan names, suggests a common origin with Oirats of western Mongolia; yet, only a limited number of genetic studies have focused on this topic. Here we compare the paternal genetic relationship of Kalmyk clans with ethnographically related groups from Mongolia, Kyrgyzstan and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 35 publications
0
22
0
7
Order By: Relevance
“…3, S4). Based on the Y-STR and SNP results we conclude that most Avar N-Tat chromosomes probably originated from a common source population of people living in Southern Siberia and Mongolia 18,19 .…”
Section: Genetic Data On the Origin Of The Avar Elitementioning
confidence: 81%
See 2 more Smart Citations
“…3, S4). Based on the Y-STR and SNP results we conclude that most Avar N-Tat chromosomes probably originated from a common source population of people living in Southern Siberia and Mongolia 18,19 .…”
Section: Genetic Data On the Origin Of The Avar Elitementioning
confidence: 81%
“…According to the study by Ilumäe et al 18 , the frequency peak of N-F4205 (N3a5-F4205) chromosomes is close to the Transbaikal region of Southern Siberia and Mongolia. A recent Y-SNP study of Central Asian populations by Balinova et al found this N-F4205 subhaplogroup also frequent (52.2%) among the nomadic herder Tsaatans (Dukha or Duhalar people), living in Mongolia and the Tuva Republic 19 . We conclude based on our STR network that most Avar N-Tat chromosomes probably originated from a common source population of people living in the Mongolian and Baikal area, in line with the results of Ilumäe et al 18 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Âûñîêèé óðîâåíü ìåaeãðóïïîâîé èçìåí÷èâîñòè ïî öåëîìó ðÿäó àíòðîïîìåòðè÷åñêèõ ïðèçíàêîâ, õàðàêòåðèçóþùèõ ìîðôîëîãè÷åñêèé ñòàòóñ êàëìûêîâ è ñàðò-êàëìàêîâ, ïîäòâåðaeäàåòñÿ äàííûìè ãåíåòè÷åñêîãî àíàëèçà [Áàëèíîâà ñ ñîàâò., 2016;Balinova et al, 2019].…”
unclassified
“…Åñëè ðàññìàòðèâàòü âñå èçó-÷åííûå ïîïóëÿöèè â öåëîì, ìîaeíî êîíñòàòèðîâàòü, ÷òî áîëåå 50% âûáîðêè ïðèíàäëåaeàò ðàç-ëè÷íûì âåòâÿì ãàïëîãðóïïû Ñ3: C3 (xC3c'i, C3f1), C3c1a-Z32870, C3c'i-L1373, C3c-Ì48, C3c1b-F6379, C3h-F914 (Ì401), Ñ3c1a1-B469, C3f1-Ì407.  êàëìûöêèõ è ìîíãîëüñêèõ ïîïóëÿöèÿõ ýòà ãàïëîãðóïïà ñîñòàâëÿåò 62,5%, à ñàìîé ðàñïðîñòðàíåííîé ãàïëîãðóïïîé èç Ñ3 ÿâëÿåòñÿ C3c1b-F6379 -40,3%, êîòîðóþ ìîaeíî ñ÷èòàòü îéðàòñêîé âåòêîé [Balinova et al, 2019].…”
mentioning
confidence: 99%